Investigating the effect of PDA/KH550 dual functionalized h-BCN nanosheets and hybrided with ZnO on corrosion and fouling resistance of epoxy coating: Experimental and DFT studies. Issue 6 (December 2022) - Mirzaee, Majid; Seif, Abdolvahab; Rashidi, Alimorad; Silvestrelli, Pier Luigi; Zhou, Ziyang; Pourhashem, Sepideh; Duan, Jizhou; Gohari, Maryam Sirati
Abstract: In this work, two-dimensional hexagonal boron carbonitride nanosheets co-functionalized with polydopamine (PDA) and 3-aminopropyltriethoxysilane (KH550) (abbreviated as Fh-BCNNS) are introduced as nanofillers for promoting the fouling and physical barrier resistance of solvent-based epoxy coatings. The material characterization conducted with X-ray techniques of photoelectron spectroscopy and diffraction as well as Brunauer–Emmett–Teller confirm that the synthesized h-BCNNS has 353 m 2 /g specific surface area with microporous structure, while field emission scanning electron microscopy and Fourier transform infrared spectroscopy indicate that the co-functionalization is successfully achieved. After dispersing the Fh-BCNNS in the epoxy matrix at 0.3, 0.6, and 1.0 wt% followed by mixing with the curing agent, the coating is applied by a spray method on the steel surface. The data derived by electrochemical impedance spectroscopy show that the optimum corrosion resistant properties is achieved by loading 0.6 wt% Fh-BCNNS, and the coating resistance of the optimized nanocomposite is 3.7 × 10 7 and 2.85 × 10 6 Ω.cm 2 after immersion in the corrosive electrolyte of 3.5 wt% NaCl aqueous solution for 1 day and 28 days, respectively. Furthermore, density functional theory (DFT) alongside the experimental investigations proves the mechanisms involved in corrosion protection properties through considering interactions and electronic properties. For EP/Fh-BCNNS@F-ZnO nanohybrid, the value of Zf = 0.01 Hz of EP/Fh-BCNNS@F-ZnO hybrids after 1 day and 4 weeks of immersion, are 9 × 10 7 and 3.3 × 10 7 Ω.cm 2 which are two order of magnitude higher than EP/Fh-BCNNS. According to anti-fouling results, the growth rate of algae is less than 10% for the EP/Fh-BCNNS@F-ZnO sample and between 30% and 60% for the control sample (EP/Fh-BCNNS at 0.6 wt%) after 28 days of immersion. Graphical Abstract: ga1 Highlights: The two-dimensional h-BCNNS are synthesized using inexpensive precursors. Functionalizing h-BCNNS with the contribution of PDA and APTES. EP/Fh-BCNNS coatings at 0.6% wt. exhibited good corrosion resistance. The anti-fouling properties of EP/Fh-BCNNS @F-ZnO composites were improved. The salient effects of the PDA and APTES anchored on h-BCNNS, resulting from DFT.